Propentofylline reverses delayed remyelination in streptozotocin-induced diabetic rats - Bondan, Eduardo Fernandes [UNESP]; Monteiro Martins, Maria de Fatima; Bernardi, Maria Martha [UNESP] (Sbem-soc Brasil Endocrinologia & Metabologia, 2015)
Objective: The diabetic state induced by streptozotocin injection is known to impair oligodendroglial remyelination in the rat brainstem following intracisternal injection with the gliotoxic agent ethidium bromide (EB). In such experimental model, propentofylline (PPF) recently showed to improve myelin repair, probably due to its neuroprotective, antiinflammatory and antioxidant effects. The aim of this study was to evaluate the effect of PPF administration in diabetic rats submitted to the EB-demyelinating model. Materials and methods: Adult male rats, diabetic or not, received a single injection of 10 microlitres of 0.1% EB solution into the cisterna pontis. For induction of diabetes mellitus the streptozotocin-diabetogenic model was used (50 mg/kg, intraperitoneal route - IP). Some diabetic rats were treated with PPF (12.5 mg/kg/day, IP route) during the experimental period. The animals were anesthetized and perfused from 7 to 31 days after EB injection and brainstem sections were collected for analysis of the lesions by light and transmission electron microscopy. Results: Diabetic rats injected with EB showed larger amounts of myelin-derived membranes in the central areas of the lesions and considerable delay in the remyelinating process played by surviving oligodendrocytes and invading Schwann cells after the 15th day. On the other hand, diabetic rats that received PPF presented lesions similar to those of non-diabetic animals, with rapid remyelination at the edges of the lesion site and fast clearance of myelin debris from the central area. Conclusion: The administration of PPF apparently reversed the impairment in remyelination induced by the diabetic state.
Keywords: Central nervous system; diabetes mellitus; oligodendrocytes; propentofillyne; remyelination